Proceedings of the Twenty-Fifth Annual ACM-SIAM Symposium on Discrete Algorithms 2013
DOI: 10.1137/1.9781611973402.8
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Common String Partition Parameterized by Partition Size Is Fixed-Parameter Tractable

Abstract: The NP-hard Minimum Common String Partition problem asks whether two strings x and y can each be partitioned into at most k substrings such that both partitions use exactly the same substrings in a different order. We present the first fixed-parameter algorithm for Minimum Common String Partition using only parameter k.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…). Similarly, the sequence d A(5,7) of consecutive duos is mapped into the sequence d B (3,5) of consecutive duos; hence duos (A [5], A [6]), (A [6], A [7]) of A are preserved. The number of preserved duos induced by the mapping is 3.…”
Section: Preliminariesmentioning
confidence: 99%
“…). Similarly, the sequence d A(5,7) of consecutive duos is mapped into the sequence d B (3,5) of consecutive duos; hence duos (A [5], A [6]), (A [6], A [7]) of A are preserved. The number of preserved duos induced by the mapping is 3.…”
Section: Preliminariesmentioning
confidence: 99%
“…Note that MCSP has been proved to be in FPT with respect to the size of the solution [18]. It can be seen that this result can be adapted for the SMCR problem in the case = 1.…”
Section: Duomentioning
confidence: 76%
“…Damaschke [15] presented the first fixedparameter algorithms for MCSP, for combined parameters such as "partition size plus repetition number of the input strings". 2 Subsequently, MCSP was shown to be fixedparameter tractable with the single parameter partition size [9]. Jiang et al [23] considered the combined parameter "partition size plus maximum occurrence d of any character" and showed that MCSP can be solved in time (d!)…”
Section: :2 Parameterized Complexity Of Maximum-duo Preservation String Mappingmentioning
confidence: 99%